2017
DOI: 10.1016/j.biocel.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The HDAC inhibitor SAHA does not rescue CFTR membrane expression in Cystic Fibrosis

Abstract: The development of suitable Cystic Fibrosis (CF) models for preclinical bench tests of therapeutic candidates is challenging. Indeed, the validation of molecules to rescue the p.Phe508del-CFTR channel (encoded by the Cystic Fibrosis Transmembrane conductance Regulator gene carrying the p.Phe508del mutation) requires taking into account their overall effects on the epithelium. Suberoylanilide Hydroxamic Acid (SAHA), a histone deacetylase inhibitor (HDACi), was previously shown to be a CFTR corrector via proteos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
1
15
1
Order By: Relevance
“…5c ). Although, a single recent study suggests that SAHA may not significantly rescue membrane CFTR levels but data from this study is inconclusive due to insuffiecient number of replicates and experimental variation, where SAHA mediated CFTR increase was observed in some cellular models but not other [ 43 ]. Moreover, the same study also suggests that SAHA treatment decreases CFTR mRNA levels and thus cannot be used as an efficient CFTR corrector.…”
Section: Discussionmentioning
confidence: 99%
“…5c ). Although, a single recent study suggests that SAHA may not significantly rescue membrane CFTR levels but data from this study is inconclusive due to insuffiecient number of replicates and experimental variation, where SAHA mediated CFTR increase was observed in some cellular models but not other [ 43 ]. Moreover, the same study also suggests that SAHA treatment decreases CFTR mRNA levels and thus cannot be used as an efficient CFTR corrector.…”
Section: Discussionmentioning
confidence: 99%
“…Vorinostat, belinostat, panobinostat and romidepsin are four HDACi approved by the US Food and Drug Administration (FDA) to treat cutaneous and peripheral T-cell lymphoma (75,(77)(78)(79). Vorinostat appears to abrogate the phenotypic defects associated with the F508del variant by modulating immune responses (80,81) and improving the stability and trafficking of F508del-CFTR (74,82). While a recent manuscript has reported conflicting data pertaining to the impact of Vorinostat on the F508del variant of CFTR in nasal epithelial cells, the results likely reflect expected cell-specific environments that are differentially sensitive to epigenetic alterations (82).…”
Section: Introductionmentioning
confidence: 99%
“…While CFBE410-cells are a commonly used cellular model to study the folding, trafficking and function of CFTR variants and have proven useful in the identification of small molecule therapeutics and targets to treat CFTR phenotypic defects, they express CFTR from a transgene driven by a viral promoter, which fails to recapitulate CFTR biology and its endogenous promoter activity that are likely to have tissue specific responses triggering variable levels of expression and/or the maladaptive stress response (MSR) that is known to contribute to the etiology of disease and its corrective potential through proteostasis modulation [101]. Consistent with this view, a recent report indicated that Vorinostat cannot correct nasal epithelial cell conductance when placed in transwell culture, conditions which recapitulate the nasal respiratory environment [89].…”
Section: Hdaci Rescue F508del Cftr In Primary Airway Cellsmentioning
confidence: 99%
“…Vorinostat appears to abrogate the phenotypic defects associated with the F508del variant by modulating immune responses [87,88] and improving the stability and trafficking of F508del-CFTR [89,90]. While a recent manuscript has reported conflicting data pertaining to the impact of Vorinostat on the F508del variant of CFTR in nasal epithelial cells, the results likely reflect expected cell-specific environments that are differentially sensitive to epigenetic alterations [89].…”
Section: Epigenomic Changes Are Regulated By Histone Deacetylases (Hdmentioning
confidence: 99%
See 1 more Smart Citation